A novel dental infiltration resin based on isosorbide-derived dimethacrylate with high biocompatibility, hydrolysis resistance, and antibacterial effect - Yang, Su; Sui, Baiyan; Cui, Yinan; Liu, Xin; Sun, Jiao; Wang, Jun (Frontiers in Bioengineering and Biotechnology, 2022)
Objectives: Available infiltration resin has raised biosafety and treatment stability challenges due to the cytotoxicity of main component-TEGDMA and its susceptibility to hydrolysis under the oral environment. The aim of the present study was to develop a TEGDMA-free infiltration resin to overcome these drawbacks. Methods: Based on synthetic bio-derived monomer-bis(methacrylate) isosorbide (IBM) and the zwitterionic compound 2-methacryloyloxyethyl phosphorylcholine (MPC), a novel infiltrant-IBMA was prepared and preferentially selected. We evaluated the performance of IBMA resin regarding cytotoxicity, anti-biofilm adhesion and hydrolysis resistance, and further verified its recovery effect on demineralized enamel and stability of infiltrated area under artificial aging conditions. Results: The results revealed that compared with commercial TEGDMA-based infiltration resin-ICON, IBMA not only achieved similar enamel morphologic and aesthetic restorative effect in chalky lesions, but also exhibited favorable cell viability, durable Streptococcus mutans UA159 biofilm-repellent performance and higher enamel microhardness (204.0±5.12HV) of infiltrated enamel. In particular, thanks to high crosslink density [(47.77±5.76) *103mol/mm3] and low water sorption [12.79 ±2.56 ug/mm3] of the polymer network, IBMA resin was more resistant to hydrolysis than ICON, which could prevent the infiltrant’s micropore-blocking effect from being disrupted after aging. Meanwhile, enamel lesions treated with IBMA showed good color stability after tea-staining challenge, which was significantly better than the ICON group. Conclusions: These findings fully demonstrate that IBMA resin exhibits favorable cell viability, hydrolysis resistance and biofilm-repellent property, which breaks through the defects of traditional TEGDMA system. Therefore, it’s promising to provide a better option for microinvasive treatment involving early caries and enamel whitish discoloration.